2001
DOI: 10.1164/ajrccm.163.3.2003060
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Successful Extubation in Neurosurgical Patients

Abstract: A respiratory therapist-driven weaning protocol incorporating daily screens, spontaneous breathing trials (SBT), and prompts to caregivers has been associated with superior outcomes in mechanically ventilated medical patients. To determine the effectiveness of this approach in neurosurgical (NSY) patients, we conducted a randomized controlled trial involving 100 patients over a 14-mo period. All had daily screens of weaning parameters. If these were passed, a 2-h SBT was performed in the Intervention group. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
214
1
14

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(242 citation statements)
references
References 32 publications
13
214
1
14
Order By: Relevance
“…7 In a randomized controlled trial comparing a non-physician-directed ventilator weaning protocol to routine care in a neurosurgical ICU, Namen et al reported a Glasgow coma score Ն 8 to be strongly associated with extubation success in neurosurgical patients. 22 Salam and colleagues reported that subjects unable to complete 4 task commands (open eyes, follow with eyes, grasp hand, and stick out tongue) prior to extubation were 4 times more likely to require reintubation. 6 However, the study by Coplin et al reported similar extubation failure among brain injured subjects regardless of their Glasgow coma score.…”
Section: Discussionmentioning
confidence: 99%
“…7 In a randomized controlled trial comparing a non-physician-directed ventilator weaning protocol to routine care in a neurosurgical ICU, Namen et al reported a Glasgow coma score Ն 8 to be strongly associated with extubation success in neurosurgical patients. 22 Salam and colleagues reported that subjects unable to complete 4 task commands (open eyes, follow with eyes, grasp hand, and stick out tongue) prior to extubation were 4 times more likely to require reintubation. 6 However, the study by Coplin et al reported similar extubation failure among brain injured subjects regardless of their Glasgow coma score.…”
Section: Discussionmentioning
confidence: 99%
“…1 Weaning decisions based solely on expert clinical judgment are not always correct. 3 Previous reports suggest that clinical judgment based on traditional respiratory parameters and the level of neuromuscular impairment [4][5][6][7] may prevent unnecessary delay of withdrawal from mechanical ventilation and mitigate complications such as diaphragm atrophy and weakness. 8,9 A number of procedures to verify patients' readiness for weaning have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Published November 28, 2011 Extubation failure is defined as the reinstitution of respiratory support from 24 to 72 h following the scheduled extubation. This condition occurs in 2 to 25% of extubated patients (1)(2)(3). Extubation failure increases the incidence of mortality, pneumonia, number of days in the intensive care unit (ICU) and hospital, time spent on mechanical ventilation (MV), hospital costs, and the need for a tracheostomy (4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have demonstrated an increased incidence of reintuba-tion, pneumonia, and prolonged MV among such patients (2)(3)(4)(5)7,9,14,15).…”
Section: Introductionmentioning
confidence: 99%